A Signaling Theory Perspective on Building Supportive Responses to Organizational Change: An Experimental Study - Anastasia Kieliszek (Junior Management Science (JUMS), 2021)
Organizations are frequently unsuccessful in creating employee support for change. Research has asserted that one important reason for change resistance is employee uncertainty. Yet despite wide consensus that leadership and communication are key vehicles to influence employees' change reactions, employee uncertainty concerning the leader of the change, and how this uncertainty can be addressed have been largely disregarded. Drawing on signaling theory, I propose that leaders who signal their charisma and change commitment when announcing change can alleviate uncertainty by assuring employees about the leader's characteristics and intentions, and thereby foster supportive responses to change. Specifically, I test the main and interactive influence of leader charisma and change commitment signals in determining employees' affective and normative commitment to, and behavioral support for, organizational change. In line with the proposition that charismatic signaling is inherently values-based and needs to be morally validated by followers, I investigate its effect on follower change commitment as a function of followers' openness to change and self-transcendence values. My findings from an experimental vignette study in a sample of 284 US employees reveal that in particular leader charisma signaling, and weakly leader change commitment signaling, have positive main, but non-interactive effects on follower behavioral support for change, which do not operate indirectly through follower affective and normative change commitment. Further, I report that followers' behavioral support for change elicited by leader charisma and change commitment signaling varies as a function of followers' openness to change and self-transcendence values. Above and beyond effects concerning behavioral change support, leader charisma signaling is revealed to increase followers' expression of openness to change, conservation, and self-transcendence values when advocating organizational change. I discuss implications for theory and practice in managing employee responses to organizational change.
Keywords: 650; Organizational change; leadership; charisma; signaling; commitment